CPC-111 Pharmacists' optimization of the medication process during admission to hospital: A multicentre, randomized, controlled trial. (12th March 2013) - Nielsen, TRH; Honoré, PH; Andersen, SE; Rasmussen, M
Abstract : Background: During hospital admission, nearly 10% of all patients experience adverse events (AEs) and almost 1/3 of AEs are drug related (ADEs). The effect of clinical pharmacy on ADEs and drug costs has not been substantiated in randomised controlled trials. Purpose: To study the clinical effect of pharmaceutical optimisation of the medication process at admission to hospital. Materials and Methods: Medical patients admitted to three Danish acute wards aged ≥18 years and taking ≥4 types of medicine per day were eligible for inclusion. The patients were randomised to either intervention or control group. A retrospective control group was also formed. The intervention was comprised of: medicines history, medicines review, medicines reconciliation and entry of proposed prescriptions in the electronic medication system. Primary endpoint was the proportion of patients with adverse drug events (ADEs), identified by screening the charts for 25 defined triggers from the Danish version of 'Global Trigger Tool'. ADEs were then validated and evaluated for severity scores by two independent panels of clinicians blinded for the intervention. Secondary end points were length of hospital stay (LOS), in-hospital drug costs, readmissions and death within one year of discharge. Results: From March 2010 to July 2011 a total of 1775 patients were screened for inclusion. 573 patients were included, 74 were excluded due to discharge within 24 hours, leaving 499 patients in the study. Preliminary studies clearly showed that the intervention group had fewer ADEs and triggers, shorter LOS and lower in-hospital drug costs than the control groups, although no significant differences were recorded. Conclusions: Although the findings did not reach statistical significance, the clinical pharmacist's intervention tended to have a positive impact on the medication process in terms of higher patient safety and lower health care costs. No conflict of interest.